(3GOGQI GdeTGQjY (B:s (3efgL cej (B/s - (3GdaVd, eDjOs; (3GdYHjOj, eMehO s ((3YeGf(B: s (3eDSSI GdhQGb ddfTQ h GdJhRjY(B, s, 2005)
(3eaGgje GSGSjI aj GOGQI GdeTQhY(B, (3JNWjW GdeTQhY(B, (3JfXje GdeTQhY h JfajPg GVGaI Gdi THcGJ GdYed (B/ (3GdeSGQ GdLQL(BCPM , (3Jbjje h eQGLYI JfajP GdHQGeL HjQJ (BPert (3h cPG GSdhH (BTime-Cost / Pert (3aj GdQbGHI Ydi JfajP GdeTGQjY h aj GdGNjQ GSGdjH h JbfjGJ eNJdaI aj GOGQI h JfajP GdeTGQjY(B.s
(3eQGLY U(B.369 , (3edGMb U(B.374s
Keywords: (3GOGQI GdeTQhYs; (3JfajP GdeTQhYs